Factors that affect audit quality - Calocha, Ramadhani; Herwiyanti, Eliada (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
The title of this research is factors that affect audit quality. This research aims to know, analyze, and show the effects of the relationship between experience, auditor professionalism, time budget pressure, audit tenure, and knowledge of detecting errors on audit quality. The research population is all auditors at a public accounting firm in Jakarta. This research used a purposive sampling technique with some criteria for the research sample. The research sample obtained was 89 respondents. This research used survey technique as collecting the data with sharing questionnaire and multiple linear regression with SPSS software for the data analysis technique. The result of this study indicates that auditor experience and knowledge of detecting errors have a positive effect and significant on audit quality, whereas auditor professionalism, time budget pressure have a positive effect but not significant on audit quality and audit tenure have a negative effect but not significant on audit quality to the auditors at a public accounting firm in Jakarta. This result of the research is expected to be means of self-introspection for a public accounting firm in Jakarta or other regions to increasing audit quality through attention to the auditor’s experience and knowledge of detecting errors.